La legalidad de los fondos de remediación ambiental: el caso de la OEFA en la experiencia peruana* - Martin Tirado, Richard J. (Revista de Derecho, 2019)
This paper analyzes environment protection in the Peruvian order. It focuses on the situation of the application of sanctions in environmental matters by the OEFA. It analyzes the correct exercise of this power within the framework of the principles of administrative sanctioning law. In order to do this, it makes an appropriate balance between economic development and protection of the environment. In addition, we study the enforcement regime of sanctions and their relationship with environmental remediation funds.